Pengembangan Bahan Ajar Interaktif IPA Materi Sistem Peredaran Kelas V Sekolah Dasar - Clarissa Wury Sevilla; Siti Halidjah; Dyoty Auliya Vilda Ghasya; Suparjan Suparjan; Rio Pranata (FONDATIA, 2023)
This study aims to develop interactive for science subjects related to the Circulatory System Material for Grade V of State Elementary School 30 Pontianak Selatan. This research and development used the 4D model (Four-D) consisting of define, design, develop, and disseminate stages. Quantitative data results from the lift filled in by experts and students. Qualitative data were obtained from suggestions and notes by experts and students. The instruments used were interview guidelines, questionnaires, and documentation. The feasibility level of interactive teaching materials was based on the results of assessments by material experts, design experts, and language experts, while the practicality level of teaching materials was based on the results of student assessments. The feasibility of the material in the aspect of material obtained an average value of 80% and was considered "feasible". The feasibility of the materials in the design aspects obtained an average value of 85% and was considered "feasible". The feasibility of the materials in the language aspects obtained an average value of 100% and was considered "very feasible". The practicality of teaching materials obtained an average value of 85% and was considered "Practical".